2011
DOI: 10.1090/s1056-3911-2011-00553-5
|View full text |Cite
|
Sign up to set email alerts
|

On the non-analyticity locus of an arc-analytic function

Abstract: Let X be a real analytic manifold. A function f : X → R is called arcanalytic if it is real analytic on each real analytic arc. In real analytic geometry there are many examples of arc-analytic functions that are not real analytic. They appear while studying the arc-symmetric sets and the blow-analytic equivalence.In this paper we show that the non-analyticity locus of an arcanalytic function is arc-symmetric. We also discuss the behavior of the non-analyticity locus under blowings-up. By a result of Bierstone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…1.1], there exists a finite composition of blowings-up σ :Ř → R (with smooth Nash centres) which converts the arc-analytic semialgebraic function f • π| E into a Nash function f • π • σ|Ě, where the Nash manifoldĚ is the strict transform of E by σ. Moreover, by [15,Thm. 1.3], the centres of the blowings-up in σ can be chosen so that σ is an isomorphism outside the preimage of S(f • π).…”
Section: Proof Of Theoremmentioning
confidence: 85%
See 1 more Smart Citation
“…1.1], there exists a finite composition of blowings-up σ :Ř → R (with smooth Nash centres) which converts the arc-analytic semialgebraic function f • π| E into a Nash function f • π • σ|Ě, where the Nash manifoldĚ is the strict transform of E by σ. Moreover, by [15,Thm. 1.3], the centres of the blowings-up in σ can be chosen so that σ is an isomorphism outside the preimage of S(f • π).…”
Section: Proof Of Theoremmentioning
confidence: 85%
“…Given f ∈ A a (X), let S(f ) denote the locus of points x ∈ Reg k (X) such that f is not analytic at x. Then, S(f ) is semialgebraic and dim S(f ) ≤ k − 2 (see [15], and cf. [13,Thm.…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…In order to define “equivariant” generalizations of the zeta functions for Nash germs, we use an additive invariant defined on all - sets, that is Boolean combinations of arc-symmetric sets (see [16] and [17]) equipped with an algebraic action of : the equivariant virtual Poincaré series. It is defined in [9] using the equivariant virtual Betti numbers, which are the unique additive invariant on - sets coinciding with the dimensions of their equivariant homology.…”
Section: Equivariant Zeta Functionsmentioning
confidence: 99%
“…He showed, in particular, that blow-Nash equivalence is an equivalence relation and that it has no moduli for Nash families with isolated singularities. Using as a motivic measure the virtual Poincaré polynomial of McCrory and Parusiński in [20], extended to the wider category of sets [16] and [17] by Fichou in [7], one can generalize the zeta functions of Koike and Parusiński in [13]. In [8], Fichou showed that these latter zeta functions are invariants for blow-Nash equivalence via blow-Nash isomorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an arc-analytic function on R n need not be continuous [5] or subanalytic [17], and its nonanalyticity locus can be nondiscrete even if n = 2 [18]. However, arc-analytic functions that are also semialgebraic proved to be very useful in real algebraic and analytic geometry (see [1,2,4,8,12,13,15,19,20,21] and the references therein). By [16,Proposition 5.1], every semialgebraic arc-analytic function is continuous.…”
mentioning
confidence: 99%